Typification of Ficus L. (Moraceae) names published by the Colombian botanist Armando Dugand, and a new record for Colombian Flora - Plata-Castro, Ángelo Danilo; Díaz-Rueda, Daniel Mauricio; Mitidieri-Rivera, Nicole; Mansano, Vidal De Freitas; Pederneiras, Leandro Cardoso (Phytotaxa, 2025)
Ficus (Moraceae) comprises approximately 140 accepted species and around 750 binomials in Tropical America. In Colombia, at least 69 species have been recorded. Taxonomic studies of Ficus in the country were carried out by Armando Dugand between 1942 and 1955, in which he described 81 new taxa, including two from Ecuador. However, many of the taxa he described lack clear typification. In the present study, we reviewed typification of all Ficus names published by Dugand. Then, we designated lectotypes for the following nine names: Ficus caldasiana, F. calimana, F. cuatrecasasiana, F. duquei var. obtusiloba, F. garcia-barrigae, F. garcia-barrigae var. ovoidea, F. jaramilloi, F. peroblonga, and F. ocoana. Additionally, we designated epitypes for F. magdalenica and F. ypsilophlebia. We also identified F. atrox, F. guayaquilensis and F. vallis-caucae as names that should be excluded from the genus, clarifying the nomenclatural framework. Furthermore, under Special notes on F. cartagenensis and F. schultesii, we address two nomenclatural cases involving misapplied and mislabelled type material to prevent future regarding their correct typification and application. Finally, we present the first record of F. nigrotuberculata Pelissari & Romaniuc for the Colombian Flora, collected in the department of Vaupés. This species was previously known only from the Amazonian biome in Bolivia, Brazil, and Peru.